On the linguistic status of ‘agreement’ in sign languages - LILLO-MARTIN, DIANE (2011)
In signed languages, the arguments of verbs can be marked by a system of verbal modification that has been termed “agreement” (more neutrally, “directionality”). Fundamental issues regarding directionality remain unresolved and the phenomenon has characteristics that call into question its analysis as agreement. We conclude that directionality marks person in American Sign Language, and the ways person marking interacts with syntactic phenomena are largely analogous to morpho-syntactic properties of familiar agreement systems. Overall, signed languages provide a crucial test for how gestural and linguistic mechanisms can jointly contribute to the satisfaction of fundamental aspects of linguistic structure.